Binge Ethanol Exposure in Mice Represses Expression of Genes Involved in Osteoblast Function and Induces Expression of Genes Involved in Osteoclast Differentiation Independently of Endogenous Catalase. (10th November 2021) - Denys, Alexandra; Pedersen, Kim B; Watt, James; Norman, Allison R; Osborn, Michelle L; Chen, Jin-Ran; Maimone, Cole; Littleton, Shana; Vasiliou, Vasilis; Ronis, Martin J J
Abstract: Excessive ethanol consumption is a risk factor for osteopenia. Since a previous study showed that transgenic female mice with overexpression of catalase are partially protected from ethanol-mediated trabecular bone loss, we investigated the role of endogenous catalase in skeletal ethanol toxicity comparing catalase knockout to wild-type mice. We hypothesized that catalase depletion would exacerbate ethanol effects. The mice were tested in a newly designed binge ethanol model, in which 12-week-old mice were exposed to 4 consecutive days of gavage with ethanol at 3, 3, 4, and 4.5 g ethanol/kg body weight. Binge ethanol decreased the concentration of serum osteocalcin, a marker of bone formation. The catalase genotype did not affect the osteocalcin levels. RNA sequencing of femoral shaft RNA from males was conducted. Ethanol exposure led to significant downregulation of genes expressed in cells of the osteoblastic lineage with a role in osteoblastic function and collagen synthesis, including the genes encoding major structural bone proteins. Binge ethanol further induced a smaller set of genes with a role in osteoclastic differentiation. Catalase depletion affected genes with expression in erythroblasts and erythrocytes. There was no clear interaction between binge ethanol and the catalase genotype. In an independent experiment, we confirmed that the binge ethanol effects on gene expression were reproducible and occurred throughout the skeleton in males. In conclusion, the binge ethanol exposure, independently of endogenous catalase, reduces expression of genes involved in osteoblastic function and induces expression of genes involved in osteoclast differentiation throughout the skeleton in males.